Biosensor development for the analysis of food quality - Giakoumaki, Elsa (Cranfield University, 2003)
This thesis describes the development and evaluation of a number of biosensors for food applications. The first part of this thesis deals with the development of Surface Plasmon Resonance (SPR) biosensor systems, coupled with Polymerase Chain Reaction (PCR) for the detection of GMO related amplified nucleic acids in foodstuffs. The first SPR Biosensor described, used streptavidin-biotin linkage chemistry to attach a P35S nucleic acid probe on dextran-coated SPR transducer chips. Methodologies were developed for both the PCR stage and post-PCR sample preparation for the sensitive, rapid and cost-effective detection of GMO-specific amplified DNA sequences. The final embodiment of the method was an asymmetric PCR amplification system with a simple sample processing step (0.3 M NaOH for 30 min in 20 % v/v formamide). The developed PCR-SPR system was successfully applied to the screening of samples of GMO origin. The second SPR biosensor reported herein, is based on a SPR chip immobilised single-stranded thiolated DNA. The thiolated probe exhibited a hybridisation capacity of 95 RU (Resonance Units) for 100 nM of complementary DNA target and a detection limit of 5 nM. The potential of the current probe system for the detection of symmetrically amplified DNA sequences of short length was subsequently confirmed. The second part of this thesis involved preliminary studies into the development of simple, disposable screen-printed electrodes for the electrochemical determination of glucose and L-amino acids in horticultural products. The dynamic range of the developed biosensors was up to 10 mM for glucose and up to 1 mM for L-leucine determination. The developed glucose biosensor exhibited encouraging analytical performance in fresh fruit samples. However, the L-amino acid oxidase electrodes consistently underestimated the amino acid content of the fruit samples. The latter observation was found to be primarily due to inhibitory components in the matrix.